Year in Review 2021: Noteworthy Literature in Cardiothoracic Anesthesia. (June 2022) - Smoroda, Aaron; Douin, David; Morabito, Joseph; Lyman, Matthew; Prin, Meghan; Ahlgren, Bryan; Young, Andrew; Christensen, Elijah; Abrams, Benjamin A; Weitzel, Nathaen; Clendenen, Nathan
In 2021, progress in clinical science related to Cardiac Anesthesiology continued, but at a slower rate due to the ongoing pandemic and disruptions to clinical research. Most progress was incremental and addressed persistent questions related to our field. To identify articles for this review, we completed a structured review using our previously reported methods (1). Specifically, we used the search terms: "cardiac anesthesiology and outcomes" (n = 177), "cardiothoracic anesthesiology" (n = 34), "cardiac anesthesia, " and "clinical outcomes" (n = 42) filtered on clinical trials and the year 2021 in PubMed. We also reviewed clinical trials from the most prominent clinical journals to identify additional studies for a narrative review. We then selected the most noteworthy publications for inclusion in this review and identified key themes.